A single Gal4-like transcription factor activates the Crabtree effect in Komagataella phaffii. Issue 1 (December 2018) - Ata, Özge; Rebnegger, Corinna; Tatto, Nadine; Valli, Minoska; Mairinger, Teresa; Hann, Stephan; Steiger, Matthias; Çalık, Pınar; Mattanovich, Diethard
Abstract The Crabtree phenotype defines whether a yeast can perform simultaneous respiration and fermentation under aerobic conditions at high growth rates. It provides Crabtree positive yeasts an evolutionary advantage of consuming glucose faster and producing ethanol to outcompete other microorganisms in sugar rich environments. While a number of genetic events are associated with the emergence of the Crabtree effect, its evolution remains unresolved. Here we show that overexpression of a single Gal4-like transcription factor is sufficient to convert Crabtree-negativeKomagataella phaffii (Pichia pastoris) into a Crabtree positive yeast. Upregulation of the glycolytic genes and a significant increase in glucose uptake rate due to the overexpression of the Gal4-like transcription factor leads to an overflow metabolism, triggering both short-term and long-term Crabtree phenotypes. This indicates that a single genetic perturbation leading to overexpression of one gene may have been sufficient as the first molecular event towards respiro-fermentative metabolism in the course of yeast evolution. Aerobic ethanol production, a phenomenon referred as Crabtree effect, allows yeast to outcompete other microorganisms in sugar rich environments. Here, the authors show that overexpression of a Gal4-like transcription factor can transformKomagataella phaffii from Crabtree effect negative to positive.